Choice of Law and Intellectual Property Rights - Annette Kur; Ulf Maunsbach (Oslo Law Review)
An increased number of intellectual property rights infringements challenges modern society and its legal institutions. The development is enhanced by digitalisation, following in the footsteps of the emerging information society and the ease by which intellectual property rights can be shared. The fact that sharing is a borderless activity has made it crucial to find solutions to a growing number of cross-border disputes. The development unfolds in two ways: the enhancement of legal initiatives as regards substantive intellectual property protection, and an increasing interest in private international law. In this article, this development is discussed with a specific focus on choice-of-law issues that arise in cross-border infringement cases. The solution of applying the law of the protecting country as a principle rule that is found in Article 8 in the Rome II Regulation is thoroughly analysed, and some alternative ways to solve ‘choice of law’ issues are presented in light of the development of a new choice-of-law regime in Norway.